Morfodinâmica do Rio Aguapeí: processos e formas resultantes / Tainá Medeiros Suizu. - - Suizu, Tainá Medeiros [UNESP] (2015)
The Aguapeí River floodplain, located in São Paulo state - Brazil, is characterized by high frequency of oxbow lakes, which suggest the occurrence of crucial changes in flow and sediment regimes of the river. However, due to lack of studies aiming to understand its morphodynamic, the timescale of these changes as well their causes and implications in channel morphology are unknown. In this sense, the present study aimed to identify the adjustments occurred in meanders morphology of Aguapeí River due to the influence of the main controls on fluvial system. The methodological support of the research was the principles of general systems theory. The assessment of the forms in river longitudinal profile was carried out through the correlation to the physical environment data in a regional scale; the establishment of the graded river profile and; the application of Hack index. Based on that, three anomalies were detected, which are related to the differential erosion and the channel control exerted by structural features. In order to understand the channel geomorphic response to such anomalies, a regression analysis of the valley gradient to sinuosity index was established. It showed a negative correlation between these variables due to differences in the lithological compositions of the riverbed. In detailed scale, the spatio-temporal changes in the morphology of two specific reaches of the river - in the upper-middle course and lower course next to mouth - were quantified. It was verified that the channel has undergone significant changes over three years - 1962, 1979/1986 and 2010. The causes of these changes can be both allogeneic as autogenic. Regarding the allogeneic ones, the climate was considered the main cause of channel changes... (Complete abstract click electronic access below)